Retraction: A versatile strategy for alternately arranging the foam ratio layers of multilayer graphene/thermoplastic polyurethane composite foams towards lightweight and broadband electromagnetic wave absorption. Issue 24 (15th April 2021) - Wang, Chaozhi; Li, Jiang; Guo, Shaoyun
Abstract : Retraction of 'A versatile strategy for alternately arranging the foam ratio layers of multilayer graphene/thermoplastic polyurethane composite foams towards lightweight and broadband electromagnetic wave absorption' by Chaozhi Wang et al., RSC Adv., 2019, 9, 23843–23855, DOI: ; 10.1039/C9RA04405A .